DIPLOMA PROJECT TEAM WORK MANAGEMENT - Kruglyk В.С. (Journal of Information Technologies in Education (ITE), 2015)
During the work performance students should get the maximal approach to the process of real project execution, so the project should include the need to use the latest technology, integration of data or services with different developments, architecture design, interaction of the team members and others. Implementation of graduation projects is the useful activity for the acquisition and consolidation of key IT competencies. Since the task of educational projects is maximal close to real one, students participate almost in all typical stages of commercial product’s development, and do so successfully. This is also confirmed practically: students, who were actively engaged in some projects at the university, have key positions in IT companies of the city and country after that. The main objective of the paper is to describe the organization of a common group students’ work on a degree project, implementation peculiarity of such projects, recommendations for improving the quality of projects. Thus, the paper is devoted to the peculiarities of the joint students’ work on a project during diploma execution in IT specialties, as the final part of the acquisition and consolidation process of key IT competencies of future programmers. The problem of choosing work topic, project concept, work organization in a group, implementation process organization has been considered. Also the specific stages of software development have been considered: development of interface, choice of technology, product quality, project disposal to the next developers, project completion.